Implementasi Model Quantum Teaching Berbantu Media Romakita Terhadap Hasil Belajar Siswa Tema Udara Bersih Bagi Kesehatan Kelas V SD Negeri Kawengen 02 Semarang - Dhevita Rina Lestari; Intan Rahmawati; Fine Reffiane (STKIP Andi Matappa Pangkep, 2021)
This study aims to determine the implementation of the quantum teaching model with Romakita media on learning outcomes for fifth grade students. The theme of clean air for health at SD Negeri Kawengen 02. This type of research uses experimental quantitative research with One-Group Pretest - Posttest design. Data collection techniques in this study used test, interview and documentation techniques in the online learning process. The data analysis technique in this study used the initial data normality test, the final data normality test, the t test and the learning completeness test. The obstacle in this research is that students have difficulty participating in learning with online methods and the media used cannot be directly used by students.